An approximate in-situ method for investigating irradiation damage of grain boundary. (December 2021) - Zhang, Lei; Du, Yufeng; Han, Wentuo; Liu, Pingping; Yi, Xiaoou; Yabuuchi, Kiyohiro; Ohnuki, Somei; Wan, Farong
Highlights: An approximate in-situ method, MCII was proposed to investigate irradiation damage. MCII uses a conventional ion accelerator and a separated TEM. MCII can be applied to investigate the irradiation effects of grain boundaries. The feasibility of MCII was verified in both low- and high-angle boundaries. Abstract: Grain boundary plays an important role in irradiation damage. The presented work proposes an approximate in-situ method, mesh-covered ion irradiation (MCII) for investigating the irradiation damage. The method was applied to a Fe-9 wt.% Al model alloy. During irradiation, transmission electron microscopy (TEM) samples prepared by twin-jet electro-polishing were covered by 400-Cu gilder grids with a pitch of 62 µm, a hole width of 37 µm, and a bar width of 25 µm. After He irradiations, in both the high-angle boundary and the sub-grain boundary, the irradiated and non-irradiated zones can be simultaneously generated. The MCII method provides an approximate in-situ method to investigate irradiation damage of grain boundaries when separately using a conventional ion accelerator and a TEM.